Effects of Neuromuscular Electrical Stimulation on Quadriceps Muscle Strength and Mass in Healthy Young and Older Adults: A Scoping Review. Issue 9 (9th June 2021) - Rahmati, Masoud; Gondin, Julien; Malakoutinia, Fatemeh
Abstract: Objective: Although neuromuscular electrical stimulation (NMES) has been used as a safe and relevant complement to voluntary resistance training, its effectiveness in increasing quadriceps femoris muscle strength and mass in healthy young and older adults has not been determined. The aim of this scoping review was to assess the effects of NMES on quadriceps muscle strength and mass in healthy young and older adults. Methods: CENTRAL, Pedro, MEDLINE, and PubMed were searched from inception to September 2019. Randomized controlled trials (RCTs) that compared NMES with control group or voluntary resistance training for healthy young and older adults were included. Study characteristics, primary and secondary outcome parameters, and details of the NMES intervention were extracted by 2 reviewers. Only studies for which full text was available in English were included. Results: Thirty-two RCTs including 796 healthy participants were identified as being eligible for young adults, and 5 RCTs including 123 healthy participants were identified as being eligible for older adults. The available evidence strongly suggests that NMES improves quadriceps muscle strength compared with a control group in young adults, but its efficacy seems lower than that of voluntary resistance training. The available limited evidence regarding the effects of NMES on quadriceps muscle mass compared with control in young adults is inconclusive, with 3 RCTs showing positive effects and 3 RCTs not showing positive effects. The very limited available evidence from 5 RCTs in older adults suggests that NMES might be beneficial for increasing quadriceps muscle strength and mass. Conclusion: Overall, the evidence indicates that NMES is an efficacious method for increasing quadriceps muscle strength in young adults, whereas its impact on muscle mass requires further investigations. In addition, the effectiveness of NMES needs to be confirmed in older adults on the basis of more high-quality RCTs with larger sample sizes. Impact: This scoping review of 37 RCTs including 919 people is the first study, to the authors' knowledge, to show that the use of NMES increases quadriceps muscle strength in young adults and might improve quadriceps muscle strength compared with control interventions in older adults. In both young and older adults, the effects of NMES on quadriceps muscle mass are still unclear.